Who wins? predicting strategic success and failure in armed conflict - Sullivan, Patricia L., Ph. D. (New York ; Oxford : Oxford University Press, 2012)
Patricia L. Sullivan argues that the key to understanding strategic success in war lies in the nature of the political objectives states pursue through the use of military force.
Description based on online resource; title from PDF title page (viewed on July 16, 2012).
Includes bibliographical references and index.
Keywords: Strategy; Military policy -- Case studies; Conflict management -- Case studies; Military history, Modern -- 20th century; War